Prednisone in Duchenne Dystrophy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
The results of a randomized controlled trial of daily Prednisone conducted in 99 boys aged five to 15 years with Duchenne dystrophy are reported from the Department of Neurology, University of Rochester, NY and five collaborating institutions.